Household Electrification and Education Outcomes: Panel Evidence from Uganda - Faisal Buyinza; Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2018)
We investigate the impact of household electrification on educational outcomes in Uganda using household panel data and employ a probit model. The findings indicate that electrification increases school enrolment at all education cycles. Also, education level of household head, marital status, gender and good housing increase education outcomes. Our results provide insights on the existing gaps in designing supportive policies for increased access to electricity for rural households where there are high disproportionately poor education outcomes. The results suggest that policies to eliminate all barriers to access to electricity will greatly enhance educational outcomes in Uganda.
Keywords: 330; Household electrification; education outcomes; gender; panel data; Uganda